An Innovative Sukuk-Waqf for Islamic Microfinance Institutions: Integrating Maqasid Al-Shariah, SDGs and Waqf - Abdul Hai; Dr. Salina Kassim; Mohammed Meeran Jasir Mohtesham (Tazkia Islamic Finance and Business Review, 2021)
Microfinance institutions (MFIs) have been widely recognized to promote financial inclusion and contribute towards poverty eradication by facilitating the access to financial products and services to the under-privileged and unbankable segment of society. Nevertheless, numerous studies have shown that many MFIs face the issue of economic viability and financial sustainability due to the lack of fund mobilization. By considering the success of conventional MFIs, several countries have introduced Islamic MFIs by adopting the Islamic modes of financing on the asset side of the conventional MFIs model. However, they face the same problems as their conventional counterparts on their liability side. The present study aims to introduce a Sukuk-waqf model as a source of funds for the Islamic MFIs through as cash waqf. In achieving this objective, the study adopts a qualitative research approach and proposes a Sukuk-waqf model for the development of Islamic MFIs. The combination of cash Waqf with Sukuk for raising funds for the Islamic MFIs is expected to contribute to the economic sustainability and viability of the institutions. In modelling the Sukuk-waqf model, the study attempts to integrate SDGs, Waqf, and Maqasid al-shariah, which emphasis on the poverty eradication, social justice, and economic welfare through the notion of Hifze deen (preservation of faith), hifze maal (preservation of wealth) and by providing access to the poor for productive resources such as education, training, and credit. The results from this study are expected to provide important inputs for the sustainable development of Islamic MFIs and assist the MFIs to contribute towards achieving the SDGs and ultimately, the Maqasid al-shariah.